Development and validation of animal welfare knowledge, attitude, and practice assessment tool among smallholder farmers in Ethiopia - Ayalew, Gezahegn; Berhe, Tsega; Mekonnen, Mesfin; Gelan, Eyob; Wieland, Barbara; Knight-Jones, Theodore J.D.; Doyle, Rebecca (2022)
Objective: To develop and validate an assessment tool to measure knowledge, attitude, and practice (KAP) towards animal welfare among smallholder farmers in Ethiopia.